Physics‐based protein structure refinement in the era of artificial intelligence. Issue 12 (29th June 2021) - Heo, Lim; Janson, Giacomo; Feig, Michael
Abstract: Protein structure refinement is the last step in protein structure prediction pipelines. Physics‐based refinement via molecular dynamics (MD) simulations has made significant progress during recent years. During CASP14, we tested a new refinement protocol based on an improved sampling strategy via MD simulations. MD simulations were carried out at an elevated temperature (360 K). An optimized use of biasing restraints and the use of multiple starting models led to enhanced sampling. The new protocol generally improved the model quality. In comparison with our previous protocols, the CASP14 protocol showed clear improvements. Our approach was successful with most initial models, many based on deep learning methods. However, we found that our approach was not able to refine machine‐learning models from the AlphaFold2 group, often decreasing already high initial qualities. To better understand the role of refinement given new types of models based on machine‐learning, a detailed analysis via MD simulations and Markov state modeling is presented here. We continue to find that MD‐based refinement has the potential to improve AI predictions. We also identified several practical issues that make it difficult to realize that potential. Increasingly important is the consideration of inter‐domain and oligomeric contacts in simulations; the presence of large kinetic barriers in refinement pathways also continues to present challenges. Finally, we provide a perspective on how physics‐based refinement could continue to play a role in the future for improving initial predictions based on machine learning‐based methods.